(untitled) (Global Journal of Human-Social Science, 2012)
Is writing an inborn or learned art Currently we can see that majority of undergraduates in higher learning institutions are rather handicapped in this area Purportedly this study proposed a teaching model to investigate the four main learning objectives 1 to generate ideas with visual aids 2 to write grammatically correct sentences using a model of sentence patterns 3 to evaluate students ability to write systematically using the writing process approach in cooperative learning groups and 4 to develop a teaching model that can prompt students to speak and write confidently and proficiently A teaching model based on the writing process approach and cooperative learning skills was implemented using the purposive writing technique It was conducted on a class of Business communication students for fifty-four hours of face-to-face interaction